Media Prasmanan Bakso dan Stupa Prestasi pada Asesmen Formatif IPS Siswa SMPN 1 Purwanegara - Fajriyatun Fajriyatun; Sriyanto Sriyanto (Universitas 45 Surabaya, 2024)
Formative assessment can help teachers understand the strengths and weaknesses experienced by students in learning. Techniques in implementing formative assessment vary, one of which can use media. Initial observation data of students who have learning difficulties in understanding the subject matter as much as 95% and learning completeness has only reached 50.00%, and the average score is 69.05%. The purpose of this study is to describe the results of learning innovation research in the form of using meatball buffet media and achievement stupa on formative assessment of social studies subjects of class IX students of SMPN1 Purwanegara. The method used was Classroom Action Research (PTK) conducted at SMP Negeri 1 Purwanegara. The population in this study were all ninth grade students of SMP Negeri 1 Purwanegara, totalling 272 students. The sample in this study were students of class IX G. Teacher-made innovative media in the form of meatball buffet and achievement stupa used in this learning research were made to determine student learning difficulties and student learning outcomes. The results of the research activities were that students only experienced learning difficulties of 2%. While the learning outcomes 90% of students showed complete learning with an average score of 87.67. In conclusion, formative assessment using prasmanan bakso media and stupa prestasi can reduce learning difficulties and help students understand the material so that their learning outcomes increase.